2019
DOI: 10.21203/rs.2.11675/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of standard and over-the-head method of chest compressions during cardiopulmonary resuscitation - a simulation study

Abstract: Background: Maintaining highly effective cardiopulmonary resuscitation (CPR) can be particularly difficult when artificial ventilation using a bag-valve-mask device, combined with chest compression have to be carried out by one person. The aim of the study is to compare the quality of CPR conducted by one paramedic using chest compression from the patient’s side with compression conducted from the ‘over-the-head’ position. Methods: The subject of the study were two methods of CPR – ‘standard’ (STD) and ‘over-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This was also mentioned in previous studies. 14 The overall CPR quality score for over the head position was significantly better than the Lateral position. Based on this study, it indicated that the CPR quality on over the head position group obtained an average CPR quality score of 4.75 (79% of the maximum range) with a standard deviation of 1.36.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This was also mentioned in previous studies. 14 The overall CPR quality score for over the head position was significantly better than the Lateral position. Based on this study, it indicated that the CPR quality on over the head position group obtained an average CPR quality score of 4.75 (79% of the maximum range) with a standard deviation of 1.36.…”
Section: Discussionmentioning
confidence: 91%
“…8 In other studies, different results emerged were more respondents performed chest compressions correctly on Over the head position CPR compared to respondents who performed Lateral position CPR. 14 This study analyzed the distinctions in CPR quality between the Head position and Lateral position on Nursing Students at Universitas Muhamadiyah Malang.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be investigated if and how complete chest recoil can be detected (e.g., sensor fusion or gyroscope). Other scenarios of the rescuer such as while standing (ambulance / hospital) [3], or kneeling behind the patient [4] may also be looked at.…”
Section: Discussionmentioning
confidence: 99%